A TPU material with both thermal conductivity and self-cleaning properties and its preparation method and application

By adding heat -conducting fillers and hydrophobic oil fillers to the TPU material, and using the technique of dual screw extruder and ultrasonic cleaner, the existing thermal conductivity lacks self -cleaning capacity, realize the efficient heat conduction of materials and self -cleaning The effect extends the service life of electronic products.

CN119143963BActive Publication Date: 2025-01-24SHANDONG INOV POLYURETHANE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411638878.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-24
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Existing thermal fillers lack self-cleaning ability in electronic products, resulting in a pool of pollutants on the surface of the material, affecting heat transfer and equipment stability.

Method used

Using TPU material composed of polyester polyol, isocyanate, chain extender, processing aid, catalyst, thermal conductive filler and hydrophobic and oleophobic filler, through the combined process of twin-screw extruder and ultrasonic cleaner, a thermally conductive material is prepared and self-cleaning materials.

Benefits of technology

Improve the thermal conductivity and self -cleaning capacity of TPU materials, extend the service life of electronic products, and enhance the corrosion resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of polyurethane elastomer and its preparation, and specifically relates to a TPU material with both thermal conductivity and self-cleaning, and its preparation method and application. The TPU material with both thermal conductivity and self-cleaning described in the present invention is made of the following components in parts by weight: 50-57 parts of polyester polyol; 32-37 parts of isocyanate; 10-12 parts of chain extender; 0.8-1.2 parts of processing aid; 0.01-0.02 parts of catalyst; 10-20 parts of thermal conductive filler; 5-10 parts of hydrophobic and oleophobic filler; The TPU material with both thermal conductivity and self-cleaning provided by the present invention has both thermal conductivity and self-cleaning functions, while improving the heat dissipation performance, reducing the pollution on the surface of the material, and extending the service life of electronic products. The present invention also provides its preparation method and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane elastomers and preparation thereof, and specifically relates to a TPU material having both thermal conductivity and self-cleaning properties, and a preparation method and application thereof. Background Art

[0002] In today's electronic technology field, with the popularization of the third-generation Internet technology (Web3) and the fifth-generation communication technology (5G), electronic components are moving towards high integration, diversified functions, and light weight and flexibility. This trend has put forward new requirements for thermal conductive fillers, especially in portable electronic devices such as smartphones. Due to the dense internal components and high operating power consumption, heat management has become a key issue that needs to be solved urgently.

[0003] Although traditional thermal conductive fillers can meet basic heat dissipation needs to a certain extent, as the performance of electronic products improves and the size decreases, the performance requirements for thermal conductive fillers are also increasing. Especially in highly integrated electronic devices, effective heat dissipation is crucial to maintaining stable operation of the equipment and extending its service life. However, existing thermal conductive fillers often lack self-cleaning capabilities. During long-term use, dust, grease and other pollutants are easily accumulated on the surface of the material, which not only affects the appearance, but more importantly, it hinders the effective transfer of heat and reduces the efficiency of thermal management.

[0004] Thermoplastic polyurethane (TPU) elastomer is a linear polymer formed by the interlocking copolymerization of hard segments and soft segments. TPU has physical properties such as tensile strength, wear resistance and heat resistance, and elasticity similar to rubber. TPU can be processed by thermoplastic material processing technology, such as injection molding, extrusion, blow molding, calendering and slush molding. With the increase in usage, TPU has become an important part of the material industry, and is mainly used in shoe materials, 3C sheaths, pipes and films.

[0005] TPU has also been widely used in the manufacture of electronic products, mainly in the insulation layer and protective layer materials, shell materials, key and button materials, seal and gasket materials, connector and fixing materials, touch screen protective film materials, and buffer materials. However, the thermal conductivity and self-cleaning ability of traditional TPU materials still need to be improved. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a TPU material with both thermal conductivity and self-cleaning functions. The material can improve the heat dissipation performance while reducing the pollution on the surface of the material and extending the service life of electronic products. The present invention also provides a preparation method and application thereof.

[0007] The TPU material having both thermal conductivity and self-cleaning properties of the present invention is made of the following components in parts by weight:

[0008] 50-57 parts of polyester polyol;

[0009] 32-37 parts of isocyanate;

[0010] Chain extender 10-12 parts;

[0011] Processing aids 0.8~1.2 parts;

[0012] Catalyst 0.01~0.02 parts;

[0013] Thermal conductive filler 10~20 parts;

[0014] 5-10 parts of hydrophobic and oleophobic filler;

[0015] The hydrophobic and oleophobic filler is prepared by using tetraethyl orthosilicate and polydimethylsiloxane as organic components and hydrophobic nano silicon dioxide particles as inorganic components through hydrolysis and condensation under alkaline conditions to perform organic-inorganic hybridization.

[0016] The polyester polyol is one of saturated aliphatic polyester polyol, unsaturated aliphatic polyester polyol, aromatic polyester polyol or mixed acid polyester polyol, the number average molecular weight of the polyester polyol is 1000-4000, preferably saturated aliphatic polyester polyol. Specifically, the polyester polyol is one of polyethylene adipate glycol ester diol, polybutylene adipate-1,4-diol ester diol, polyhexylene adipate glycol ester diol, polyethylene adipate-1,4-diol ester diol, polybutylene adipate-1,4-diol-hexylene adipate glycol ester diol.

[0017] The isocyanate is one of 4,4'-diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate, toluene diisocyanate or p-phenylene diisocyanate, preferably 4,4'-diphenylmethane diisocyanate (MDI-100).

[0018] The chain extender is an alkanediol having 2 to 6 carbon atoms, specifically one of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,3-butanediol, 1,5-pentanediol or neopentyl glycol, preferably 1,4-butanediol (BDO).

[0019] The processing aid is one or more of an antioxidant, a lubricant or an ultraviolet absorber; the catalyst is one or more of an organic titanium catalyst, an organic tin catalyst or an organic amine catalyst, preferably an organic tin catalyst.

[0020] The antioxidant is a hindered phenol antioxidant and / or a phosphite antioxidant, preferably one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (1010), bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite (626), tris[2,4-di-tert-butylphenyl]phosphite (168) or didodecanol thiodipropionate (DLTDP).

[0021] The lubricant is amide wax and / or montan wax, and the preferred lubricant is one or more of WAX-C and WAX-E, and more preferably WAX-C.

[0022] The ultraviolet absorber is methyl ether and / or hindered ammonia; the preferred ultraviolet absorber is one or more of UV-1 and 770, and more preferably UV-1.

[0023] The thermal conductive filler is one or more of a carbon-based thermal conductive filler or a ceramic thermal conductive filler, preferably a ceramic thermal conductive filler, the ceramic thermal conductive filler mainly includes silicon carbide (SiC), aluminum oxide (Al2O3), aluminum nitride (AlN), and can also be preferably a boron nitride nanosheet (BNNSs) made by hexagonal boron nitride (h-BN), more preferably BNNSs, carbon-based thermal conductive filler graphene. The step of using hexagonal boron nitride (h-BN) to make boron nitride nanosheets (BNNSs) is as follows: weigh 1.0g~2.0gh-BN powder in a beaker, and add 200~300mL of a mixed solution of isopropanol / deionized water with a mass ratio of 1:1~1:2, and after sufficient stirring, place it in an ultrasonic cell crusher with an ultrasonic power of 600~1000W for ultrasonic peeling, the time is set to 4~6h, and the ultrasonic temperature is 23~30℃. After the ultrasonic is completed, The obtained solution was placed in a desktop high-speed centrifuge for centrifugation. First, it was centrifuged at a speed of 3000-5000 rpm for 15-30 minutes to remove larger particles in the solution. Then, the supernatant was centrifuged at a speed of 9000-12000 rpm for 30-60 minutes to obtain a crude thermal conductive filler by ultrasonic peeling. The obtained crude thermal conductive filler was fully washed with deionized water for multiple times to remove residual isopropanol, and then placed in an electric heated blast drying oven at 65-80°C to obtain a BNNSs thermal conductive filler.

[0024] The mass ratio of the organic component to the inorganic component in the hydrophobic and oleophobic filler is 1:3-1:4, and the mass ratio of tetraethyl orthosilicate to polydimethylsiloxane in the organic component is 1:1-1:2.

[0025] Specifically, the preparation method of the hydrophobic and oleophobic filler is:

[0026] The first step is to add 5-10 g of nano-silicon dioxide into a beaker containing 50-100 mL of anhydrous ethanol, stir it thoroughly with a magnetic stirrer at room temperature for 30-60 min, and then place it in an ultrasonic instrument for 20-30 min to ensure that the silicon dioxide is evenly dispersed in the anhydrous ethanol;

[0027] In the second step, 1-2 g of tetraethyl orthosilicate and 1-2 g of polydimethylsiloxane were added dropwise into a beaker;

[0028] The third step is to add 0.6-1.0 g of ammonia water and 9-13 g of deionized water to the above solution at the same time, and stir continuously for 1-2 h with a magnetic stirrer at room temperature to obtain a super hydrophobic and oleophobic slurry;

[0029] The fourth step is to place the prepared super hydrophobic and oleophobic slurry in a dryer for drying to obtain a hydrophobic and oleophobic filler.

[0030] The preparation method of the TPU material with both thermal conductivity and self-cleaning comprises the following steps: dissolving a processing aid in polyester polyol and injecting the processing aid into a twin-screw extruder together with a chain extender, injecting isocyanate into the twin-screw extruder, and injecting a catalyst into the twin-screw extruder; the mixed materials are reacted and plasticized in the screws, and granulated by an underwater cutting system to obtain TPU particles; the obtained TPU particles are dispersed in a solvent, and after dissolving, a thermal conductive filler and a hydrophobic and oleophobic filler are added, mixed evenly, and the solvent is volatilized to obtain a TPU material with both thermal conductivity and self-cleaning.

[0031] The extrusion temperature of the twin-screw extruder is 130~220℃, and the screw speed is 170~230rpm; the obtained TPU particles are dispersed into a DMF and ethyl acetate mixed solvent with a mass ratio of 1:1~1:2, and a thermal conductive filler and a hydrophobic and oleophobic filler are added after dissolution, and mixed evenly by ultrasound. The mass ratio of DMF and ethyl acetate mixed solvent is 1:1~1:2. When a DMF and ethyl acetate mixed solvent with a mass ratio of 1:1 is selected, the TPU particles can reach a maximum mass solubility of 25%, thereby increasing the maximum yield. Compared with the traditional method, the solubility is increased. Of course, a DMF and ethyl acetate mixed solvent with a mass ratio of 1:2 can also be selected. Although the yield after dissolution is not the best choice, there will be no qualitative reduction in the performance of the obtained TPU material with both thermal conductivity and self-cleaning, so the optimal mass ratio of the dissolved mixed solvent is 1:1.

[0032] Application of the TPU material having both thermal conductivity and self-cleaning properties: the prepared TPU material having both thermal conductivity and self-cleaning properties is used to produce mobile phone protective covers.

[0033] Specifically, the method for preparing the TPU material having both thermal conductivity and self-cleaning properties comprises the following steps:

[0034] (1) After the processing aid is dissolved in the polyester polyol, it is injected into a twin-screw extruder together with the chain extender. At the same time, isocyanate is injected into the twin-screw extruder. The catalyst is injected into the twin-screw extruder through an external device. The mixed materials are reacted and plasticized in the screw, and granulated by an underwater cutting system to obtain TPU particles; the extrusion temperature of the twin-screw extruder is 130~220℃, and the screw speed is 170~230rpm.

[0035] (2) Disperse the obtained TPU particles in a mixed solvent of DMF and ethyl acetate in a mass ratio of 1:1~1:2, heat to 30~50℃ to accelerate dissolution, add thermal conductive filler and hydrophobic oleophobic filler to the solution after complete dissolution, place in a high-frequency CNC ultrasonic cleaner and ultrasonicate at a power of 250~400W for 60~100min to evenly disperse the thermal conductive filler and hydrophobic oleophobic filler, fully mix, place the treated solution in a 100℃ oven to accelerate solvent evaporation, and obtain a TPU material with both thermal conductivity and self-cleaning properties after the solvent evaporates completely. The purpose of the temperature after dispersion described in step (2) is to accelerate dissolution, and the purpose of the parameters of the ultrasonic cleaner is also to disperse evenly, and no further exploration of specific parameters is made. Those skilled in the art are familiar with the operation of ultrasonic cleaners.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) In the preparation method of the TPU material having both thermal conductivity and self-cleaning properties of the present invention, TPU particles are dissolved in a special solvent of a 1:1 mixture of DMF and ethyl acetate, and the mass fraction of TPU in the solution can reach 25%, which greatly improves the yield compared with the traditional DMF system;

[0038] (2) The TPU material with both thermal conductivity and self-cleaning properties prepared by the method of the present invention is added with thermal conductive fillers, which greatly improves the directional thermal conductivity of TPU; and the hydrophobic and oleophobic materials are added, which greatly improves the hydrophobic and oleophobic properties of TPU.

[0039] (3) The TPU material with both thermal conductivity and self-cleaning properties prepared by the present invention is used to prepare mobile phone covers, which can improve the directional thermal conductivity, self-cleaning ability and corrosion resistance of the covers. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific embodiments.

[0041] The weight fractions of the raw material components of the TPU material having both thermal conductivity and self-cleaning properties of the present invention are all calculated in the same mass unit in the examples and comparative examples.

[0042] Some of the raw materials used in the following examples and comparative examples are as follows, and the others are normal commercially available products.

[0043] Hindered phenol antioxidant 1010, purchased from BASF, Germany;

[0044] Phosphite antioxidant 626, purchased from BASF, Germany;

[0045] Amide wax lubricant WAX-C was purchased from Clariant, Germany;

[0046] The lignite wax lubricant WAX-E was purchased from Clariant, Germany;

[0047] Methyl ether ultraviolet absorber UV-1 was purchased from BASF, Germany;

[0048] Hindered ammonia UV absorber 770 was purchased from BASF, Germany;

[0049] Hexagonal boron nitride (h-BN) was purchased from Shanghai MacLean Biochemical Co., Ltd.;

[0050] N,N-Dimethylformamide (DMF) was purchased from Tianjin Fuyu Fine Chemical Co., Ltd.;

[0051] Isopropanol was purchased from Tianjin Fuyu Fine Chemical Co., Ltd.

[0052] Example 1

[0053] The preparation steps of the BNNSs thermal conductive filler described in Table 1 are as follows: 1.0 g of h-BN powder is weighed into a beaker, and 200 mL of a mixed solution of isopropanol / deionized water with a mass ratio of 1:1 is added. After sufficient stirring, the evenly dispersed h-BN solution is placed in an ultrasonic cell crusher with an ultrasonic power of 600 W for ultrasonic exfoliation. The duration is set to 4 h and the ultrasonic temperature is 23 ° C. After the ultrasonic treatment, the obtained solution is placed in a desktop high-speed centrifuge for centrifugation. First, the solution is centrifuged at a speed of 3000 rpm for 15 min to remove larger particles in the solution; then the supernatant is centrifuged at a speed of 9000 rpm for 30 min to obtain ultrasonic exfoliated BNNSs. The obtained BNNSs are fully washed with deionized water 3 times to remove residual isopropanol. The collected BNNSs are placed in an electric heating blast drying oven at 65 ° C to obtain BNNSs thermal conductive fillers.

[0054] Example 2

[0055] The hydrophobic and oleophobic filler a, the hydrophobic and oleophobic filler b and the hydrophobic and oleophobic filler c described in Table 1 were prepared according to the following steps.

[0056] 1) The preparation method of the hydrophobic and oleophobic filler a is as follows:

[0057] In the first step, 10 g of nano-silicon dioxide was added to a beaker containing 50 mL of anhydrous ethanol, and the mixture was stirred with a magnetic stirrer for 30 min at room temperature, and then ultrasonicated in an ultrasonic instrument for 20 min to ensure that the silicon dioxide was evenly dispersed in the anhydrous ethanol.

[0058] In the second step, 1 g of tetraethyl orthosilicate and 2 g of polydimethylsiloxane were added dropwise into a beaker;

[0059] The third step is to add 0.6 g of ammonia water and 9 g of deionized water to the above solution at the same time, and stir continuously for 1 h with a magnetic stirrer at room temperature to obtain a super hydrophobic and oleophobic slurry;

[0060] The fourth step is to place the prepared super hydrophobic and oleophobic slurry in a dryer for drying to obtain a hydrophobic and oleophobic filler a.

[0061] 2) The preparation method of the hydrophobic and oleophobic filler b is:

[0062] In the first step, 8 g of nano-silicon dioxide was added to a beaker containing 100 mL of anhydrous ethanol, and the mixture was stirred for 60 min using a magnetic stirrer at room temperature. The mixture was then ultrasonicated for 30 min in an ultrasonic instrument to ensure that the silicon dioxide was evenly dispersed in the anhydrous ethanol.

[0063] In the second step, 1 g of tetraethyl orthosilicate and 1.6 g of polydimethylsiloxane were added dropwise into a beaker;

[0064] The third step is to add 1.0 g of ammonia water and 13 g of deionized water to the above solution at the same time, and stir continuously for 2 h with a magnetic stirrer at room temperature to obtain a super hydrophobic and oleophobic slurry;

[0065] The fourth step is to place the prepared super hydrophobic and oleophobic slurry in a dryer for drying to obtain a hydrophobic and oleophobic filler b.

[0066] 3) The preparation method of the hydrophobic and oleophobic filler c is:

[0067] In the first step, 8 g of nano-silicon dioxide was added to a beaker containing 60 mL of anhydrous ethanol, and the mixture was stirred with a magnetic stirrer for 40 min at room temperature, and then ultrasonicated in an ultrasonic instrument for 25 min to ensure that the silicon dioxide was evenly dispersed in the anhydrous ethanol.

[0068] In the second step, 1.6 g of tetraethyl orthosilicate and 1 g of polydimethylsiloxane were added dropwise into a beaker;

[0069] The third step is to add 0.6 g of ammonia water and 10 g of deionized water to the above solution at the same time, and stir continuously for 1 h with a magnetic stirrer at room temperature to obtain a super hydrophobic and oleophobic slurry;

[0070] The fourth step is to place the prepared super hydrophobic and oleophobic slurry in a dryer for drying to obtain a hydrophobic and oleophobic filler c.

[0071] The thermally conductive and self-cleaning TPU material described below is made from the components in Table 1 in parts by weight.

[0072] Table 1 Raw material components of Examples 1-3 and Comparative Examples 1-3

[0073]

[0074] Example 3

[0075] The raw material components of the examples and comparative examples in Table 1 were prepared according to the following method for preparing TPU materials, which specifically includes the following steps:

[0076] (1) After the processing aid is dissolved in the polyester polyol, it is injected into a twin-screw extruder together with the chain extender, and the isocyanate is injected into the twin-screw extruder at the same time. The catalyst is injected into the twin-screw extruder through an external device. The mixed materials are reacted and plasticized in the screw, and granulated by an underwater cutting system to obtain TPU particles; the extrusion temperature of the twin-screw extruder is 130~220℃, and the screw speed is 170~230rpm, wherein the extrusion temperature and screw speed of Examples 1-3 and Comparative Examples 1-3 are carried out according to Table 2.

[0077] (2) The obtained TPU particles are dispersed in a mixed solvent of DMF and ethyl acetate in a mass ratio of 1:1, and the temperature is raised to 50°C to accelerate dissolution. After complete dissolution, thermal conductive filler and hydrophobic and oleophobic filler are added to the solution, and the solution is placed in a high-frequency CNC ultrasonic cleaner and ultrasonicated at a power of 250 W for 60 minutes to uniformly disperse the thermal conductive filler and hydrophobic and oleophobic filler, fully mix them, and completely evaporate the solvent to obtain a TPU material that is both thermally conductive and self-cleaning.

[0078] Table 2 Extrusion temperature and screw speed parameters

[0079]

[0080] The TPU materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively, and the methods are as follows:

[0081] (1) Hardness test: The test is carried out according to the method specified in standard ASTM D2240.

[0082] (2) Mechanical strength test: The test was conducted in accordance with the method specified in standard ASTM D412.

[0083] (3) Material thermal conductivity test: The thermal diffusivity of different samples was tested using an LFA467 laser thermal conductivity meter (NETZSCH, Germany). The sample to be tested was cut into a circular sheet with a diameter of 12.7 mm, a thin layer of graphite was sprayed evenly on the surface of the sample, and the sample was placed stably in a sample carrier and then placed in the test instrument. The thermal conductivity of the sample to be tested was calculated using the formula λ=a×Cp×ρ. In the formula, λ-thermal conductivity; a-thermal diffusivity; Cp-specific heat capacity; ρ-density.

[0084] (4) Material thermal conductivity stability test: Two methods were used: (a) folding the sample in half and restoring it to its original state, and (b) stretching the sample by 50% and restoring it to its original length. Each of the two experimental operations was performed 300 times. The thermal conductivity of the sample before and after the test was tested to examine the stability of the material's thermal conductivity.

[0085] (5) Material application performance test: The surface temperature of the sample to be tested during the heating process was tested using an E6390 thermal infrared imager (FLIR Systems, USA). The sample to be tested was placed on the surface of a constant temperature heating table, and thermal conductive gel was evenly applied between the sample and the surface of the heating table to ensure close contact between the two. The temperature of the constant temperature heating table was set to 50°C, and the shooting distance was 20 cm. At the same time, the temperature measuring probes of the JK804 K-type thermocouple (Changzhou Jin Ai Lian Co., Ltd.) were connected to different samples to record the real-time temperature of the samples.

[0086] (6) Material self-cleaning performance test: Cut the sample to be tested into a rectangular shape of 50mm×30mm (length×width), and use double-sided tape to stick it evenly on the surface of the slide. Place the slide in a culture dish at a certain tilt angle, with the upper end located at the upper edge of the culture dish wall and the lower end located at the bottom of the culture dish. Use methyl orange-dyed fine sand as a simulated pollutant, and take an appropriate amount and randomly spread it on the sample surface. After that, draw deionized water through a rubber-tipped dropper, and slowly squeeze the water flow from the upper end of the slide to make it pass smoothly through the sample surface; at the same time, use a camera to record the experimental phenomenon. In order to investigate the effect of the material's self-cleaning performance on the thermal conductivity, take the experimental sample after the experiment and dry it, test the thermal conductivity of the material, and compare the thermal conductivity coefficient of the test material before and after contamination.

[0087] (7) Material surface wetting performance test: The static contact angle (CA) of the water drop on the surface of the sample to be tested was characterized using an OCA20 video optical contact angle meter (Dataphysics, Germany). The sample to be tested was uniformly cut into a rectangular shape of 50 mm × 5 mm (length × width), with the surface to be tested facing upward and the sample strip was pasted on the surface of the glass slide with double-sided tape. The glass slide was placed horizontally on the test table of the video optical contact angle meter, and 8 μL of deionized water was slowly dripped onto the sample surface to observe the CA value of the water drop on the sample surface. The sliding angle (SA) of the water drop on the surface of the sample to be tested was characterized using a rolling angle meter. The preparation method of the sample to be tested was similar to that of the CA value characterization. 10 μL of deionized water was measured and dropped on the upper end of the surface of the sample to be tested. The tilt angle of the rolling angle meter was slightly adjusted until the water drop could roll on the sample surface. The tilt angle of the rolling angle meter at this time was recorded as the SA value. Five different points were selected on the surface of each sample to be tested, and the average values ​​were taken as the CA and SA values ​​of the sample. Using the same test method, water was replaced with glycerin to perform experiments and tests to characterize the oleophobic properties of the material.

[0088] (8) Material superhydrophobic stability test: Two methods were used: (a) folding the sample in half and restoring it to its original state, and (b) stretching the sample by 50% and restoring it to its original length. Each of the two experimental operations was performed 300 times. The contact angle and rolling angle of the sample were tested respectively, and the data retention rate was used as the basis for evaluating the hydrophobic and oleophobic stability of the material.

[0089] The data results of various properties of the above examples and comparative examples are shown in Table 3.

[0090] Table 3 Performance test data of Examples 1 to 3 and Comparative Examples 1 to 3

[0091]

[0092] By comparing and analyzing the performance test data of Examples 1 to 3 and Comparative Examples 1 to 3, it can be seen that:

[0093] (1) Comparative analysis of the data of Example 1 and Comparative Example 1 shows that under the same hardness conditions, the amount of thermally conductive filler added will affect the thermal conductivity of the material, that is, the thermal conductivity coefficient. Within a certain range, the more thermally conductive filler is added, the stronger the thermal conductivity of the material. At the same time, the amount of hydrophobic and oleophobic filler added will affect the surface microstructure of the material, that is, the contact angle and rolling angle are used to characterize it. Within a certain range, the more hydrophobic and oleophobic filler is added, the better the hydrophobic and oleophobic performance of the material is, and the stronger the self-cleaning ability is.

[0094] (2) By comparing and analyzing the data of Example 2 and Comparative Example 2, it can be seen that under the same hardness conditions, the amount of hydrophobic and oleophobic filler added will affect the surface microstructure of the material, that is, the contact angle and the rolling angle are used to characterize it. Within a certain range, the more hydrophobic and oleophobic filler is added, the better the hydrophobic and oleophobic performance of the material is, and the stronger the self-cleaning ability is.

[0095] (3) By comparing and analyzing the data of Example 3 and Comparative Example 3, it can be seen that under the same hardness conditions, the amount of thermal conductive filler added will affect the thermal conductivity of the material, that is, the thermal conductivity coefficient. Within a certain range, the more thermal conductive filler is added, the stronger the thermal conductivity of the material.

[0096] (4) By comparing and analyzing the data of Example 1 and Comparative Example 2, it can be seen that the type of thermally conductive filler will affect the thermal conductivity of the material, that is, the thermal conductivity coefficient. The BNNSs in the present invention make the material have better thermal conductivity.

[0097] (5) By comparing and analyzing the data of Example 1 and Comparative Example 3, it can be seen that the type of hydrophobic and oleophobic filler will affect the surface microstructure of the material, that is, the contact angle and the rolling angle are used to characterize it. The hydrophobic and oleophobic filler a in the present invention makes the material have better hydrophobic and oleophobic performance and stronger self-cleaning ability.

Claims

1. A TPU material with both thermal conductivity and self-cleaning properties, characterized in that: It is made of the following components in parts by weight: 50-57 parts of polyester polyol; 32-37 parts of isocyanate; Chain extender 10-12 parts; Processing aids 0.8~1.2 parts; Catalyst 0.01~0.02 parts; Thermal conductive filler 10~20 parts; 5-10 parts of hydrophobic and oleophobic filler; The hydrophobic and oleophobic filler is prepared by organic-inorganic hybridization with tetraethyl orthosilicate and polydimethylsiloxane as organic components and hydrophobic nano-silica particles as inorganic components through hydrolysis and condensation under alkaline conditions; the mass ratio of the organic component to the inorganic component in the hydrophobic and oleophobic filler is 1:3-1:4, and the mass ratio of tetraethyl orthosilicate and polydimethylsiloxane in the organic component is 1:1-1:

2.

2. The TPU material having both thermal conductivity and self-cleaning properties according to claim 1, characterized in that: The polyester polyol is one of saturated aliphatic polyester polyol, unsaturated aliphatic polyester polyol, aromatic polyester polyol or mixed acid polyester polyol, and the number average molecular weight of the polyester polyol is 1000-4000.

3. The thermally conductive and self-cleaning TPU material according to claim 1, characterized in that: The isocyanate is one of 4,4'-diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate, toluene diisocyanate or p-phenylene diisocyanate.

4. The thermally conductive and self-cleaning TPU material according to claim 1, characterized in that: The chain extender is an alkanediol having 2 to 6 carbon atoms.

5. The thermally conductive and self-cleaning TPU material according to claim 1, characterized in that: The processing aid is one or more of an antioxidant, a lubricant or an ultraviolet absorber; the catalyst is one or more of an organic titanium catalyst, an organic tin catalyst or an organic amine catalyst.

6. The thermally conductive and self-cleaning TPU material according to claim 1, characterized in that: The thermally conductive filler is a carbon-based thermally conductive filler or a ceramic-based thermally conductive filler.

7. A method for preparing a TPU material having both thermal conductivity and self-cleaning properties according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: dissolving a processing aid in polyester polyol and injecting the mixture into a twin-screw extruder together with a chain extender, injecting isocyanate into the twin-screw extruder, and injecting a catalyst into the twin-screw extruder, reacting and plasticizing the mixed materials in the screws, and granulating the materials through an underwater cutting system to obtain TPU particles, dispersing the obtained TPU particles into a solvent, adding a thermal conductive filler and a hydrophobic and oleophobic filler after the particles are dissolved, mixing the particles evenly, and volatilizing the solvent to obtain a TPU material having both thermal conductivity and self-cleaning properties.

8. The method for preparing the thermally conductive and self-cleaning TPU material according to claim 7, characterized in that: The extrusion temperature of the twin-screw extruder is 130-220° C., and the screw speed is 170-230 rpm; the obtained TPU particles are dispersed in a mixed solvent of DMF and ethyl acetate, and after dissolving, thermal conductive fillers and hydrophobic and oleophobic fillers are added, and mixed evenly by ultrasound.

9. An application of the thermally conductive and self-cleaning TPU material according to any one of claims 1 to 6, characterized in that: The obtained TPU material with both thermal conductivity and self-cleaning properties is used to produce mobile phone protective cases.

Citation Information

Patent Citations

  • Hydrophobic coating and application thereof

    CN101143989A

  • Heat-conductive polyurethane elastomer for mobile phone jacket and preparation method thereof

    CN109181279A